Avaliação do grau de vulnerabilidade da zona costeira do Maranhão às mudanças climáticas - SOUSA, Luan Victor Pereira de (2024)
The IPCC Sixth Assessment Report, in turn, changes the perspective that climate change results in a potential future, but rather in the present. The dangers of rising sea levels that are already being sent to regional communities reveal the high degree of vulnerability for the natural, social and economic spheres of society. The coastline of the Maranhão Legal Amazon, to the north, is made up of many ecosystems, such as coastal forests, mangroves, wetlands, restingas and fields. Changes in ecosystems can affect important services that influence estuaries, mangroves and salt marshes. In the present work, two computational models will be used, the first being the InVEST software, to assess maritime vulnerability, the second BR-MANGUE, to simulate the response of the mangrove ecosystem to rising sea levels. The results highlight the importance of all coastal ecosystems, especially mangroves, and the damage resulting from their losses. When carrying out the tests with and without the presence of ecosystems in the InVEST software, the mangrove was the ecosystem that stood out the most and made the most difference in terms of its presence in the coastal zone. It was possible to identify that most of the coastal zone of the study area would have an intermediate risk value (for the IPCC's most alarming scenario) without the presence of all coastal ecosystems. The results also indicate that the protection provided to coastal ecosystems is highly relevant to providing nature-based solutions to combat the impacts of climate change in the Amazon coastal zone. External actions for the protection and sustainable use of these ecosystems must be increased. A more detailed evaluation of the results allowed us to better understand the dynamics of coastal ecosystems, such as mangroves in the face of rising sea levels in relation to the continent, and also how this data can be used as information to improve conservation and preservation management of the mangrove and propose subsidies for the creation of zones of more or less vulnerability along the coast of Maranhão.